Genome-wide identification of the TIFY family reveals JAZ subfamily function in response to hormone treatment in Betula platyphylla - Guanbin Lv; Rui Han; Jingjing Shi; Kun Chen; Guifeng Liu; Qibin Yu; Chuanping Yang; Jing Jiang (BMC Plant Biology, 2023)
Abstract Background The TIFY family is a plant-specific gene family and plays an important role in plant growth and development. But few reports have been reported on the phylogenetic analysis and gene expression profiling of TIFY family genes in birch (Betula platyphylla). Results In this study, we characterized TIFY family and identified 12 TIFY genes and using phylogeny and chromosome mapping analysis in birch. TIFY family members were divided into JAZ, ZML, PPD and TIFY subfamilies. Phylogenetic analysis revealed that 12 TIFY genes were clustered into six evolutionary branches. The chromosome distribution showed that 12 TIFY genes were unevenly distributed on 5 chromosomes. Some TIFY family members were derived from gene duplication in birch. We found that six JAZ genes from JAZ subfamily played essential roles in response to Methyl jasmonate (MeJA), the JAZ genes were correlated with COI1 under MeJA. Co-expression and GO enrichment analysis further revealed that JAZ genes were related to hormone. JAZ proteins involved in the ABA and SA pathways. Subcellular localization experiments confirmed that the JAZ proteins were localized in the nucleus. Yeast two-hybrid assay showed that the JAZ proteins may form homologous or heterodimers to regulate hormones. Conclusion Our results provided novel insights into biological function of TIFY family and JAZ subfamily in birch. It provides the theoretical reference for in-depth analysis of plant hormone and molecular breeding design for resistance.